Quantificação, espacialização e especiação das emissões atmosféricas de origem veicular na Região Metropolitana da Grande Vitória - Araújo, Igor Baptista de (2016)
The main objective of this study was to investigate the atmospheric emissions of vehicular origin in the metropolitan area of Greater Vitoria (RMGV) in the state of Espírito Santo, and provide it a system that characterize quantitatively in time and space, and represent their chemical nature (speciation) in these two fields. Vehicle emissions rates were recalculated using official and update methodology of Brazil, provided by the Ministry of Environment, identifying changes in inventory obtained by applying the new methodology to estimate vehicular sources. Within the Sparse Matrix Operator Kernel Emissions – SMOKE model, with the chemical speciation of all inventoried sources, besides simulating the spatial and temporal evolution of the emission of pollutants RMGV, based on the updated inventory sources. The results generated from the new estimates were compared with data from the official inventory provided by the local environmental agency (IEMA). Overall, the annual emissions calculated for vehicles in this study was lower than estimated in the inventory captained by IEMA, affecting also the distribution of the participation of non-vehicular emission sources in RMGV.